LOCAL PROCESSING OF NON-METAL MATERIALS WITH CONCENTRATED ENERGY FLOW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the present study, the peculiarities of local heat treatment with a concentrated light energy flow of non-metallic materials are traced. Mathematical dependences are presented for determining the surface density of the absorbed power - W(r), the thermal power - Po, and other characteristics in case of local thermal impact on the surface of non-metallic materials with a concentrated light energy flow.